The Psychological Effects of Empowerment Strategies on Consumers’ Product Demand - Fuchs, Christoph; Prandelli, Emanuela; Schreier, Martin (Journal of Marketing, 2010)
Companies have recently begun to use the Internet to integrate their customers more actively into various phases of the new product development process. One such strategy involves empowering customers to cooperate in selecting the product concepts to be marketed by the firm. In such scenarios, it is no longer the company but rather its customers who decide democratically which products should be produced. This article discusses the first set of empirical studies that highlight the important psychological consequences of this power shift. The results indicate that customers who are empowered to select the products to be marketed show stronger demand for the underlying products even though they are of identical quality in objective terms (and their subjective product evaluations are similar). This seemingly irrational finding can be observed because consumers develop a stronger feeling of psychological ownership of the products selected. The studies also identify two boundary conditions for this “empowerment–product demand” effect: It diminishes (1) if the outcome of the joint decision-making process does not reflect consumers’ preferences and (2) if consumers do not believe that they have the relevant competence to make sound decisions.